Controlling Blue Berets: The Consequences of Political Neglect in the Case of Uruguay's Participation in Peacekeeping. Issue 3 (July 2021) - González Guyer, Julián; Jenne, Nicole
Peacekeeping has widely been seen as conducive to submit the military to democratic rule. We put the assumption to an empirical test based on the case of Uruguay, today a fully democratic state that has consistently ranked among the world's top peacekeeping contributors per capita. Specifically, we ask whether participation in peacekeeping has increased civilian control over the military. To answer this question, we focus on three aspects of democratic civil–military relations: civilian oversight, civilian policy management, and armed forces–society relations. We conclude that peacekeeping has done little to trigger greater involvement of civilians in the area of military and defense policy but that it contributed to reduce the gap between the armed forces and society. Nevertheless, due to political neglect by civilian authorities, the state of civil–military relations is one of subordinate military autonomy short of ideal, even if it does not represent a threat to democratic rule.